Behind the criminal economy: using UK tax fraud investigations to understand money laundering myths and models - Matanky-Becker, Rian (Crime, law and social change, 2022)
To launder money is, by definition, to obfuscate and to hide, which makes it a notoriously difficult topic to study. Data access is another challenge contributing to the underdeveloped base. This paper presents an in-depth exploratory analysis of previously untapped data from the UK’s tax enforcement agency. We examine a sample of money laundering investigations (n = 31) over a three-year period, together involving 52 suspects. Against these cases, we test the applicability of the most widely used international model of money laundering: the three-stage model of placement, layering and integration (FATF, 2019). We also examine who was responsible for the offences and which laundering methods they used. A focus group with professionals helped us explore possible interpretations and implications of our findings. Overall, the results undermine the utility and validity of the ubiquitous three-stage model: it applied in under a third of cases. Cash couriers featured heavily and thus merit further attention, as do the cost-benefit decisions behind choosing between different money laundering methods. This study has relevance for academics, law enforcement, policy-makers and industry professionals alike.